Sipahalima in Parmalim Teachings: An Analysis of Local Spiritual Resilience Against the Challenges of Modernization in the City of Medan - Kurniawan, Dwi; Harahap, Indra (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the meaning, function, and dynamics of the Sipaha Lima ritual within the Parmalim belief system in Medan City, as well as the adaptation strategies employed by its community in an urban and modern context. This research is significant because Sipaha Lima is not only a spiritual practice but also a marker of local cultural identity that is vulnerable to marginalization amid globalization and dominant socio-cultural pressures. The study adopts a qualitative approach based on anthropological theory, particularly Victor Turner’s concept of ritual and theories of cultural identity. Data were collected through participant observation, in-depth interviews with key informants from the Parmalim community, and document analysis. The findings reveal that Sipaha Lima functions as a medium for community unity, internal solidarity, and the transmission of Batak noble values to the younger generation. The Parmalim community also demonstrates creative adaptation efforts through the use of digital technology and openness to interfaith dialogue. The study concludes that the continuation of the Sipaha Lima ritual reflects the cultural and spiritual resilience of the Parmalim community, while also serving as a form of resistance against stigmatization and the erosion of local values. Broader recognition and systematic documentation are necessary to ensure the preservation of this practice within Indonesia’s diverse cultural framework.